A COMPARATIVE STUDY OF EPIC WORKS BASED ON THE “ALPOMISH” PLOT (Based on Uzbek, Karakalpak, and Tatar folklore) - Allambergenova Nodira Gulmurzaevna (International Journal of Literature and Language Studies, 2026)
In the epic heritage of the peoples of the world, large-scale epic works built on narrative plots occupy an important place. In particular, heroic epics in the oral tradition of Turkic peoples, transmitted from generation to generation and refined over thousands of years, have significantly influenced not only Turkic but also world cultural and artistic thinking. The epic “Alpomish” is a vivid example of a classical epic and a literary-aesthetic monument that reflects national identity, embodying the people’s spiritual and moral strength, culture, strong will, and high ideals. This article provides a comparative analysis of epic works based on the “Alpomish” plot, which have reached us in different versions and variants in the form of a doston (epic poem) in Uzbek and Karakalpak folklore and as a heroic tale in Tatar folklore. The study identifies their similarities and distinctive features.